Bupropion for Attention Deficit Hyperactivity Disorder (ADHD) in adults - Verbeeck, Wim (Cochrane Database Syst Rev, 2011)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To examine the efficacy and safety of noradrenergic/dopaminergic reuptake inhibitors (DARI) for the treatment of adults with ADHD.